Sovereignty and extortion: a new state form in Mexico : the 2021 lectures at El Colegio Nacional - Lomnitz-Adler, Claudio (Public Planet Bks., 2024)
Claudio Lomnitz proposes a new theorization of the Mexican state in relation to extreme violence, showing how the current crisis represents a fundamental shift in the relationship between the state and the economy in which the rule of law has eroded.